La Crítica de Federico Schelling a la filosofía de Hegel - Miranda Fonseca, Héctor Eduardo (2016)
The present article tries to approach the most important from Federico Schelling to the philosophy of Guillermo F. Hegel. This critic from Schelling is done from his late thinking in where he develops the idea of a positive philosophy against a negative one. The first corresponds to his (Schelling's) own thinking, while the second has to do with the Hegelian philosophy. These two philosophies confront each other from the source of their birth. With Schelling, his philosophy emerges from the "being" and that's why it's positive; with Hegel according to Shelling, the philosophic emerges from the "nothing". It's the beginning of the Hegelian philosophy the nothing that doesn't have determinations. This leads to two different roads, one that is absurd according to Schelling, that in this case is the Hegelian, and another that is fruitful that consists in his own philosophy. Schelling in some way parts from the idea that from the nothing, something can't emerge, for it has not ontological statute. From this that in Hegel the only thing valid is the method, but not the premises.